Growth and exopolysaccharide production by Streptococcus thermophilus ST1 in skim milk - Zhang,Tiehua (2011)
To analyze the exopolysaccharide (EPS) production by Streptococcus thermophilus ST1, cultures were cultivated in 10% (w/v) reconstituted skim milk under different growth conditions including various temperatures and pHs of growth medium, supplementation of the medium with various carbon sources (glucose, lactose, sucrose, galactose and fructose) and nitrogen source (whey protein concentrate, or WPC). The results showed that most EPS production by strain ST1 was obtained at a temperature (42°C) and pH (6.5) optimal for its growth. Supplementation of the skim milk medium with either carbohydrates or WPC increased both growth and polymer formation by different extents, with sucrose being most effective among the carbon sources tested. Under the optimal cultural conditions, i.e. pH 6.5, 42°C with 2% (w/v) sucrose and 0.5% (w/v) WPC, 135.80 mg l-1 of EPS was produced by strain ST1. The monosaccharide composition of the EPS was determined to be glucose and galactose (2:1), and the molecular mass of the EPS was 3.97 × 10(6) Da. The aqueous solution of the EPS at 1% (w/v) showed relatively high viscosity, indicating the potential of this EPS-producing S. thermophilus strain for applications in the improvement of physical properties of fermented milk products.